Physio-pathological effects of alcohol on the cardiovascular system : its role in hypertension and cardiovascular disease - Kawano, Yuhei (Hypertension research, 2010)
Alcohol has complex effects on the cardiovascular system. The purpose of this article is to review physio-pathological effects of alcohol on cardiovascular and related systems and to describe its role in hypertension and cardiovascular disease. The relationship between alcohol and hypertension is well known, and a reduction in the alcohol intake is widely recommended in the management of hypertension. Moreover, alcohol has both pressor and depressor actions. The latter actions are clear in Oriental subjects, especially in those who show alcohol flush because of the genetic variation in aldehyde dehydrogenase activity. Repeated alcohol intake in the evening causes an elevation in daytime and a reduction in nighttime blood pressure (BP), with little change in the average 24-h BP in Japanese men. Thus, the hypertensive effect of alcohol seems to be overestimated by the measurement of casual BP during the day. Heavy alcohol intake seems to increase the risk of several cardiovascular diseases, such as hemorrhagic stroke, arrhythmia and heart failure. On the other hand, alcohol may act to prevent atherosclerosis and to decrease the risk of ischemic heart disease, mainly by increasing HDL cholesterol and inhibiting thrombus formation. A J- or U-shaped relationship has been observed between the level of alcohol intake and risk of cardiovascular mortality and total mortality. It is reasonable to reduce the alcohol intake to less than 30 ml per day for men and 15 ml per day for women in the management of hypertension. As a small amount of alcohol seems to be beneficial, abstinence from alcohol is not recommended to prevent cardiovascular disease.